Physique of Conscripts and Changes in Nutrition - Górny, Stanisław; Dobrzańska, Alina (Anthropological Review, 1981)
The material for this study consisted of body height and weight of conscripts measured in 1925 (N = 1,300,000), 1950 (N = 17,465), 1963 (N = 6,676), 1968 (N = 250,000), 1971 (N = 250,000), and 1976 (N = 30,742). Evaluation of nutrition level and structure of nutrition is based on balance data collected by the Central Statistical Office for the whole population of Poland. It has been found that during the last two decades, acceleration of physical development occurred among young Polish males. This trend is indicative of changes in socio-economic conditions reflected in nutritional levels.